PERAN PENDIDIKAN DAN DAKWAH DIGITAL DALAM MEMBENTUK IDENTITAS KEISLAMAN GENERASI MUDA MUSLIM - M. Syarif; Al Zahra Malika Putri; Arfah Hidayah; Wahyuni Batubara (Yayasan Baitul Hikmah al-Zain, 2026)
The rapid development of digital technology has brought major transformations to human life, including in the fields of Islamic education and da’wah. Young Muslims, as active users of digital media, are among those most affected by the global flow of information. This study aims to examine in depth the role of education and digital da’wah in shaping the Islamic identity of young Muslim generations in the modern era. The research employs a qualitative descriptive method through literature review, interviews, and observation of youth religious activities on various digital platforms such as YouTube, Instagram, TikTok, and online learning media. The findings indicate that education and digital da’wah play a strategic role in strengthening Islamic values, fostering spiritual awareness, and building moral character aligned with Islamic teachings. Digital da’wah presented with creative approaches, simple language, and engaging visuals effectively increases youth interest in religious learning. However, significant challenges also arise, including the spread of unreliable religious content, the influence of digital hedonism, and the lack of media literacy among young users. Therefore, collaboration among Islamic educational institutions, digital preachers, and families is essential to guide young Muslims in using technology wisely. This study is expected to serve as a foundation for developing effective strategies for Islamic education and da’wah in the digital era to strengthen Islamic identity among the younger generation sustainably and contextually.